Efek Kualitas Layanan, Kualitas Produk, Diskon dan Lokasi pada Kepuasan Pelanggan - Buyung Romadhoni; Ibrahim Ibrahim; Deasy Mauliana (Al-Buhuts, 2023)
The purpose of this study was to study the consequences of service quality on customer satisfaction at Domino's Pizza Makassar; consequences of product quality on customer satisfaction Domino's Pizza Makassar; the effect of the discount strategy on customer satisfaction at Domino's Pizza Makassar; the effect of location on customer satisfaction Domino's Pizza Makassar. This research method is a quantitative research method on positivism philosophy. The population sample for this study is consumers who shop at Domino's Pizza Boulevard Makassar outlets using the non-probability sampling method. The research sampling method provides a small opportunity for one population group to be sampled. The sampling technique uses a purposive sampling technique based on certain aspects in determining the sample. Selection of a group of subjects based on previously known population characteristics, and certain criteria set based on the objectives or core problems of this study. The total sample taken in this study was 50 people with the assumption that the sample represented a large number of samples that were considered appropriate in this study. The results of this study indicate that service quality, product quality, discount strategy, and business location have a positive and significant effect on customer satisfaction.